ELECTRICITY CONSUMPTION AND MANUFACTURING OUTPUT IN NIGERIA: EVIDENCE FROM ARDL ANALYSIS - ABDULLAHI, MUSA MUJTABA; FAROUK, BILKISU KABIR USMAN; DANPOME, MOSES GOSELE; ALIYU, ALIYU YAHAYA; HUSSAINI, NURA; MUHAMMAD, HALIMA HARUNA; RUNKA, AISHA ILIYASU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study examines the impact of electricity consumption and macroeconomic variables on manufacturing output in Nigeria from 1986 to 2023, using annual time series data from the World Development Indicators and the Central Bank of Nigeria. A short-run dynamic Autoregressive Distributed Lag (ARDL) model was employed due to the absence of co-integration among the variables, as revealed by the bounds test. The results indicate that electricity consumption has a positive but statistically insignificant impact on manufacturing output, with a 1% increase resulting in a 0.054% rise. Similarly, the exchange rate and inflation exhibit positive but insignificant impacts, with 1% increases associated with 0.051% and 0.012% rises in output, respectively. The current monetary policy rate (MPR) has a negative and insignificant impact, with a 1% rise reducing output by 0.016%. The first lag of MPR shows a positive but insignificant impact, while the second lag has a negative and statistically significant impact, indicating that a 1% increase in MPR at this lag reduces manufacturing output by 0.141%. This highlights the delayed negative impact of monetary tightening on industrial performance. Based on these findings, the study recommends improving electricity reliability, stabilizing exchange rates through economic diversification, and coordinating inflation management policies. Additionally, it urges the government to adopt interest rate strategies that are sensitive to the manufacturing sector.